2020
DOI: 10.1177/0825859720904802
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning to Life in a Nursing Home: The Potential Role of Palliative Care

Abstract: Background and Objectives: Transitioning to a nursing home (NH) is a major life event for 1.4 million NH residents in the United States. Most post-acute NH admissions plan for rehabilitation and discharge home, but with nearly 70% of NH residents being palliative care (PC) eligible, many evolve into long-term placements secondary to poor health and associated decline in function and/or cognition. This article describes the perceptions of NH PC-eligible residents and families transitioning to life in a NH. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…However, cultural factors or negatives ideas surrounding care homes lead to some older adults preferring being lonely within their own homes than being in the company of people they do not know [56,57]. Nevertheless, the discomfort and the measures taken to fight loneliness are, to a great extent, determined by the decision-making process of the older adults [58,59], hence why some of the participants referred to health conditions or the circumstances of family members as being deciding factors in older adults, leading older adults to suffer imposed loneliness [56,58,60]. This also occurs when their economic resources are limited and they are not able to access professional care to mitigate loneliness [56,58,61], as well as when there is a lack of availability in care homes [62].…”
Section: Discussionmentioning
confidence: 99%
“…However, cultural factors or negatives ideas surrounding care homes lead to some older adults preferring being lonely within their own homes than being in the company of people they do not know [56,57]. Nevertheless, the discomfort and the measures taken to fight loneliness are, to a great extent, determined by the decision-making process of the older adults [58,59], hence why some of the participants referred to health conditions or the circumstances of family members as being deciding factors in older adults, leading older adults to suffer imposed loneliness [56,58,60]. This also occurs when their economic resources are limited and they are not able to access professional care to mitigate loneliness [56,58,61], as well as when there is a lack of availability in care homes [62].…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that many families are willing to provide care for the older generation instead of sending loved ones to an NH (Michel et al, 2019). In a more recent study, Halifax et al (2021) concluded that participants transitioning to life in an NH and their families experienced disempowerment as they [patient and family members] perceived it as being left out of decisions to go to a NH, loss of autonomy once at the NH, and dealt with the realization that they [patients] would not be going home. (p. 64) My godmother falls under the category of loss of autonomy when making decisions regarding NH placement.…”
Section: A 72-hour Hold: Choice Theory and Essentiality-of-beingmentioning
confidence: 99%
“…I know that I am not alone in my feelings. Several studies have been published on participants describing their feeling of being unsupported, vulnerable, unprepared, and rushed discharge from the hospital (Burke et al, 2018; Gadbois et al, 2017; Halifax et al, 2021).…”
Section: A 72-hour Hold: Choice Theory and Essentiality-of-beingmentioning
confidence: 99%
“…Los CLE para personas mayores deben ser lugares en los que tanto residentes como familiares se sientan seguros para defender sus derechos y los de sus seres queridos. En esa línea, los CLE deberían contemplarse como entornos centrados en las personas mayores, donde se incorpore el apoyo desde las estructuras públicas a los referentes de centros mediante educación, formación, y financiación para innovaciones e investigación de calidad 3 . Además, los recursos de apoyo y asistencia social, así como el cuidado y la atención oportuna, son imprescindibles para asegurar una vida digna y significativa 4 .…”
unclassified